Studi Kasus Teknik Pemeriksaan Radiografi Ossa Pedis Pediatrik dengan Klinis Congenital Talipes Equino Varus (CTEV) di Rumah Sakit Islam Kendal - Irmawati, Seli; Meita Astari, Fisnandya; Maharani, Ayu (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Congenital Talipes Equino Varus (CTEV) is a congenital foot deformity that is commonly found in pediatric patients, with a fairly high prevalence in Indonesia. Radiographic examination of the foot becomes important to assess the degree of deformity and assist in therapy planning. The projections used in cases of Congenital Talipes Equino Varus (CTEV) include the anterior-posterior (AP) projection (Kite Method), lateral projection (Kite Method), and axial dorsoplantar projection (Kandel Method). The objective of this study is to identify the examination techniques for pediatric feet with clinical congenital talipes equino varus (CTEV) and to understand the reasons for using the anteroposterior (AP) and lateral (Kite method) projections. This research uses a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation on five pediatric patients diagnosed with CTEV who underwent foot radiographic examinations at the Radiology Installation of Islamic Hospital Kendal. Data analysis was conducted to compare the radiographic examination techniques applied at RSI Kendal with the recommended radiographic projection standards in the literature, as well as to assess their impact on image quality and diagnostic accuracy. Results radiographic examination of the feet in pediatric patients with CTEV at RSI Kendal was performed without any special preparation, other than removing metal objects from the area being examined. The equipment used includes a CR X-ray machine, 24x30 cm cassette, computer, printer, and image reader. The examination was conducted with two projections, namely anteroposterior (AP) and lateral, both with the patient in a supine position and the X-ray beam perpendicular to the cassette. The FFD used was 100 cm with an exposure factor of 4 mAs and 40-50 kVp. This technique is deemed sufficient to produce diagnostic images in cases of CTEV. Conclusions, pediatric foot examination techniques with two projections (AP and lateral) are deemed effective in establishing the diagnosis of CTEV and producing optimal diagnostic images. The aim of using the anteroposterior (AP) projection is to assess the talo first metatarsal angle and the talocalcaneal angle, while the lateral projection helps to evaluate the laterocalcaneal angle. To achieve better visualization of the foot anatomy, it is advisable to add an axial dorsoplantar projection to enhance the quality of visualization of the anatomical structures of the foot.